‘CHURPOON’ an Indigenous and Sustainable Water Management System in Cold Arid Ladakh - Kumar, Parveen; Angchuk, Sonam; Namgyal, D. (Journal of Agricultural Extension Management, 2022)
The Union Territory of Ladakh is characterized by a very fragile ecosystem and scarce natural resources. Agriculture here is confined to six months in a year owing to the extreme freezing temperatures which do not permit any agricultural activity in the harsh winters. The water for irrigating crops comes from the melting of snow and glaciers in summer season. The availability of this water depends upon the amount of snowfall that had occurred in the previous winter. Locals have also reported witnessing a decline in snowfall over the years. As such, the water has to be used very judiciously. This is also because of the climate change and shift in precipitation patterns. Communities in the Ladakh region have developed various institutional models for conservation of its natural resources. The present review article deliberates upon an indigenous and sustainable water management system the ‘Churpoon’. ‘Churpoon’ in the local language is used for the water supervisor, who leads the group of these water managers. These water managers are entrusted with the responsibility of irrigating the fields of the whole village judiciously